Cultivating Team Learning: Interplay of Ambidextrous Leadership and Psychological Safety (Pakistan Business Review, 2024)
This study aimed to explore the mediating role of psychological safety between ambidextrous leadership and team learning. The data were collected from 339 employees working in the service sector using a self-administered questionnaire. The scales in the questionnaire were adopted from well-known and valid sources. The data were analyzed to test the proposed hypothesis using the PROCESS Macro by Andrew Hayes in SPSS 26 and AMOS 24 for confirmatory factor analysis. The study found that there was a significant effect of ambidextrous leadership on team learning and psychological safety significantly mediated the said relationship. The study added to the literature on the theory of planned behavior by adding the novel variables of team learning and ambidextrous leadership in the context of the service sector organizations. Other studies can be initiated to explore the effects of other psychological variables like emotional intelligence and positive psychological capital to further the relevant literature. The study can be further extended to other workplaces including manufacturing and primary sector organizations.